Penyelesaian Sengketa Ekonomi Syariah Melalui Mediasi Pada Masa Pandemi di Pengadilan Agama Wilayah Yogyakarta - Ani Yunita (Fakultas Hukum Universitas Islam Indonesia, 2021)
Sharia economic dispute resolution through mediation has many advantages, but the percentage of success in the process of sharia economic dispute resolution through mediation at the Yogyakarta Regional Religious Court is still low. Furthermore, it was speculated that a pandemic condition gives influence to the mediation implementation optimally. The research was to examine the factors to the low success rate of sharia economic dispute resolution through mediation at the Yogyakarta Regional Religious Court. This research an empirical juridical study using primary data and secondary data with a statutory approach method. Data were analyzed escriptive-qualitative analysis. The results show that the settlement of sharia economic disputes through mediation at the Yogyakarta Regional Religious Court is still low due to several factors, among others, there are not many judge mediators who have mediator certificates and sharia economic certificates, the parties are not in good faith, there is no regulation regarding the presence of the parties through remote audio-visual intermediaries on the Covid-19 pandemic and the constraints of the fast handling process in the mediation process as already regulated in Supreme Court Regulation Number 1 of 2016 (PERMA No.1 Of 2016).